Secas e molhadas: estratégias ecológicas e dinâmica de comunidades vegetais em lagoas temporárias - Laís Barbalioli Macedo (2020)
Understanding the assemblage of biological communities and the organisms’ response to changes in conditions and resources have been an important foundation for ecologists to predict the ecosystems future in face of changes caused by anthropic intervention. In temporary lagoons of the Karst de Lagoa Santa Environmental Protection Area (MG), whose annual flood and drought cycles depend on groundwater levels, the current rainfall reduction has been a threat to the successional dynamics of vegetation, which alternates between aquatic and terrestrial plants. In this paper, we describe plant species composition and distribution and their ecological strategies of competition (C), stress tolerance (S) and/or ruderality (R), along flooding gradient indirectly linked to moisture in five temporary lagoons. Based on the species zonation, we identified possible on going successional sequences that, if continued, will lead to fields where plants thrive on increasingly dry soils and strategy S predominates. On the other hand, in still flooded lagoons the greatest heterogeneity habitat (aquatic, transitional and terrestrial) allows species with different ecological requirements to coexist locally. In these environments, the moisture gradient acts as a strong environmental filter and provides a greater taxonomic and functional diversity, whose strategies C and S are more representative; then increasing in S as it moves away from the flooded region. While in dry lagoons, functional convergence in S threatens the survival of the plant species found there, in the case of abiotic changes occur due to disturbances, pathogens and/or climatic changes. In addition, we demonstrate that despite all the anthropogenic pressures and impacts these lagoons are likely to, they are indispensable fragments for the wildlife survival in the region or those who pass through there. Therefore, these temporary lagoons remain important remnants of the wetland and maintaining the seasonal hydrological dynamics of temporary lagoons ensures long-term maintenance of biodiversity.